Cataloging and Subject Analysis of the Incunabula Collection of the Vasyl Stefanyk National Scientific Library of Ukraine in Lviv: MARC21, Metadata and Digital Access. - Melnyk-Khokha, Galyna (Z Badań nad Książką i Księgozbiorami Historycznymi, 2026)
This article examines the problem-oriented database Incunabula Collection of the Vasyl Stefanyk Library, launched in 2024. The research focuses on the methodology of bibliographic description were performed „de visu", with historical provenance as well as subject access analysis of 55 incunabula records performed through technical systematic cataloging in MARC21. Consistency of subject headings with international dictionaries, such as Library of Congress Subject Headings (LCSH) and basic details of access to descriptions and copies of the editions and copies recorded in ISTC and GW ensures that the Ukrainian collection is available to the rest of the scholarly community. It focuses on subject access points, such as personal, corporate, geographic, topical and uniform title headings, and locally defined thematic access of incunabula, which represents provenance of early printed books. The geographical organization of the collection is shown in the analysis that can identify the European printing centres of the 15th century especially Germany, France, Italy, and Poland. The thematic distribution shows that there was a preponderance of religious and theological literature, as well as philosophical literature and versions of antiquity. The article shows that standardized MARC21 cataloguing in combination with enhanced subject access improves researching, interoperability, and scholarly use of incunabula collections. Digitization and remote access are vital steps to the common cultural heritage maintenance in the context of the Russian-Ukrainian war.